Targeting RNA-binding proteins with small molecules: perspectives and challenges - Konde, Olivier Mpungi; Balela, Williams Balela; Tshitenge, Tania Bishola (Frontiers in Chemistry, 2025)
RNA-binding proteins (RBPs) play critical roles in numerous biological processes because they regulate RNA function by directly interacting with RNA molecules. In recent years, researchers have developed small molecules that can affect the function of RBPs, opening up promising new directions for drug discovery. While several reviews have already explored this topic, here we aim to provide additional perspectives and highlight emerging challenges in the area of targeting RBPs. There are several types of small molecule modulators that are particularly developing in this field. These include molecules that bind directly to RBPs and alter their interaction with RNA, bifunctional molecules that associate to either RNA or RBPs to disrupt or enhance their interaction, and other compounds that affect the stability of either the RNA or the RBP itself. Among these, bifunctional molecules stand out as especially promising, as they offer potential solutions to some of the common challenges faced in developing drugs targeting RBPs.